EFFECT OF FUNGICIDES, PLANT EXTRACTS AND BIOAGENTS ON SPORE GERMINATION OF COLLETOTRICHUM LINDEMUTHIANUM CAUSING FIELD BEAN ANTHRACNOSE - S. NARASIMHA RAO,; S.L. BHATTIPROLU,; A. VIJAYA GOPAL,; V. SEKHAR, (The Bioscan, 2020)
Five fungicides at three different concentrations (0.05, 0.1 and 0.15%), two leaf extracts at three different concentrations (5, 7.5 and 10%) and cultural filtrates of three bioagents were evaluated in vitro by slide germination techniques to know their efficacy against conidia of Colletotrichum lindemuthianum causing anthracnose of field bean. All the treatments were found effective and recorded significant reduction in spore germination of the test pathogen over untreated control. However, in vitro studies revealed that, significant inhibition of spore germination was observed at higher concentration fungicides and leaf extracts. Amongst fungicides, propiconazole recorded lowest spore germination (12.93%) corresponding highest inhibition (85.44%) at 0.15%, while highest spore germination (42.30%) corresponding minimum inhibition (52.57%) was noticed at 0.05% of azoxystrobin. With respect to two leaf extracts with three concentrations each, Lantana camara at 10% concentration, inhibit the spore germination by 60.38%, which was statistically on par with 7.5% concentration of L. camara (57.39%). The highest spore germination (46.60%) was recorded at 5.0 per cent concentration of A. indica. Out of three bioagents, Trichoderma viride showed highest inhibition of spore germination (53.51%) followed by Bacillus subtilis (51.16%), while least inhibition was by Pseudomonas fluorescens (40.51%).